Hukum Perkawinan Campuran dan Hak Atas Tanah di Indonesia - Ketut Oka Setiawan (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2023)
Mixed marriage in Law No. 1 of 1974 (UUP) is a marriage between two people who in Indonesia are subject to different laws, because of differences in nationality and one of the parties is a foreign citizen and one of the parties is an Indonesian citizen (Article 57 UUP). Based on this statement, according to the UUP, mixed marriage regulations prohibit brides and grooms from different religions. The prohibition is mentioned indirectly in Article 2 paragraph (1) of the UUP,